1972
DOI: 10.1107/s0567740872004625
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of 5-amino-2-thiol-l,3,4-thiadiazole

Abstract: The crystal structure of 5-amino-2-thiol-l,3,4-thiadiazole (C2H3NaS2) has been determined by threedimensional Patterson and Fourier methods and refined by block-matrix least-squares calculations.The crystals are monoclinic, space group P21/c with four molecules in a unit cell of dimensions a = 6.167, b= 10.048, c=9-007,~, fl=116.8 °. The final R index is 0.106 for 796 observed reflexions, collected with Cu K0c radiation. The molecule may be regarded as being planar since the deviations of the atoms from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The C(2)-S(2) length of 1.671 A possesses 80% double-bond character on Abraham's (1956) scale and is typical of exocyclic thiones (Downie, Harrison, Raper & Hepworth, 1972). This confirms the thione nature of the compound in the solid (Fig.…”
Section: (B) Molecular Dimensionssupporting
confidence: 65%
“…The C(2)-S(2) length of 1.671 A possesses 80% double-bond character on Abraham's (1956) scale and is typical of exocyclic thiones (Downie, Harrison, Raper & Hepworth, 1972). This confirms the thione nature of the compound in the solid (Fig.…”
Section: (B) Molecular Dimensionssupporting
confidence: 65%
“…A major class of tautomeric reactions involves the exchange of a hydrogen atom between the two other atoms in the same molecule, in both cases forming a covalent bond. The tautomeric interconversion, e.g., keto-enol, imine-enamine, and nitroso-oxime, have been extensively studied [40][41][42] and these studies showed that the tautomerism is important for the stability. The calculations showed that the tautomerism in the case of the MTA compound allows being present in the form of another isomer.…”
Section: Neutral Inhibitorsmentioning
confidence: 99%
“…For SSNH 2 acting as a ligand and as auxiliary in the construction of hydrogen bonds in coordination compounds with Pd II , see , with Pt II , see: Tannai et al (2006), with Cd II , see: Gao et al (2009) and with Au I , see: Tzeng et al (1999) ;Tzeng, Huang et al (2004). For the thiolate form, see: Downie et al (1972).…”
Section: Related Literaturementioning
confidence: 99%